EKSPLORASI KULTUR BERBASIS PROGRAM HOLISTIC INTEGRATIF DI SMP ISTIQOMAH SAMBAS PURBALINGGA - Dian Anggraini; Eti Nur Qori'ah; Fera Dwi Prasetyaningrum; Ahmad Khoiri; Ikhwandi Arifin (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2021)
The holistic, integrative program is needed for excellent schools because this program offers a variety of integrative services that support school programs to be more optimal. The service aims to know the implementation of a holistic, integrative program to support school culture at SMP Istiqamah Sambas Purbalingga, Central Java. The service method with case studies is based on findings in the field through direct observation data collection techniques and interviews with school principals, teachers, and students. The activity results show that the implementation begins with problem analysis, socialization, monitoring and evaluation of the program, and follow-up. SMP Istiqamah Sambas shows a good school culture based on monitoring and evaluating the holistic, integrative program of more than 75% achieved for each service indicator so that the holistic, integrative program effectively improves the superior school culture